PHRASEOLOGICAL EQUIVALENTS FOR PEOPLEʼS APPEARANCE IN THE RUSSIAN AND ENGLISH LANGUAGES (Scientific journal of the Fergana State University, 2023)
The article defines the concept of phraseological equivalence and explores the differences between full and partial phraseological equivalents. It also examines the semantic and structural features of the English and Russian phraseological equivalents describing the appearance of a person, and provides an etymological description of some Russian and English phraseological units.